On The Importance Of The Human Body, Nitrates - Abdumuminova R.N.; Baratova R.Sh; Bulyaev Z.K. (The American Journal of Medical Sciences and Pharmaceutical Research, 2021)
Currently, the role of food security in maintaining public health is high. Gastrointestinal and many other diseases can develop if the composition of food does not meet sanitary and hygienic requirements. As a result of the development of agro-industry, as a result of excessive and irregular application of nitrogen fertilizers, the amount of nitrate in fruits and vegetables is increasing. The negative and positive effects of nitrates on the body have been identified, and it has been found that nitrates consumed on a daily basis are important in maintaining our health.